X-ray polarimetry and spectroscopy of the neutron star low-mass X-ray binary GX 9+9: An in-depth study with IXPE and NuSTAR - Ursini F (EDP SCIENCES S A, 2025)
We report on a comprehensive analysis of simultaneous X-ray polarimetric and spectral data of the bright atoll source GX 9+9 with the Imaging X-ray Polarimetry Explorer (IXPE) and NuSTAR. The source is significantly polarized in the 4-8 keV band, with a degree of 2.2%  & PLUSMN;  0.5% (uncertainty at the 68% confidence level). The NuSTAR broad-band spectrum clearly shows an iron line, and is well described by a model including thermal disc emission, a Comptonized component, and reflection. From a spectro-polarimetric fit, we obtain an upper limit to the polarization degree of the disc of 4% (at the 99% confidence level), while the contribution of Comptonized and reflected radiation cannot be conclusively separated. However, the polarization is consistent with resulting from a combination of Comptonization in a boundary or spreading layer, plus reflection off the disc, which significantly contributes in any realistic scenario.